KINERJA, KENDALA, DAN STRATEGI PENCAPAIAN SWASEMBADA DAGING SAPI (Forum Penelitian Agro Ekonomi, 2024)
Indonesia has a big opportunity to realize cattle meat self-sufficiency, and even it is possible to become an exporter such in 1970’s. This article reviews the constraint issues in cattle industry and formulates a concept of cattle industry toward meat self-sufficiency. Cattle industry deals with typical culture and characteristics of business, policy and political issues, financial scheme, limited grassing field, breeding, development management, meat market and price, competitiveness, and inter-institutional coordination. All of those problems shift Indonesia from an exporter to an importer. In the future, political will, domestic product orientation, prioritizing small farmers through partnership, integrated farming, franchise system, cattle development project management unit are necessary to boost cattle industry. Other attempts to take by the government are special credit scheme for cattle development, grassing field development, cattle breed supply through breeding farm system development, effective and accountable cattle development management. The government needs to reformulate cattle development road map to accommodate internal and external environment issues, and to emphasize the goals of cattle industry development, such as increasing cattle population, enhancing meat product, improving cattle farmers’ income, and sustaining cattle meat self-sufficiency.